Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s43045-021-00116-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and mental health: a multi-country study—the effects of lockdown on the mental health of young adults

Abstract: Background Lockdown conditions due to the COVID-19 pandemic have affected the mental health of people, especially the youth. This study examined the effect of lockdown on mental health of Egypt, Ghana, India, Pakistan, and the Philippines and assessed the coping strategies in practice by youth. Results Philippines had the highest mean score in all three domains followed by Egypt, Pakistan, India, and then Ghana. There was a significant association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It is commonly associated with higher risk of anxiety, and depression over a period of time [ 43 ]. Other studies have also demonstrated that avoidant coping leads to higher levels of stress and affects wellbeing in a negative way [ 44 , 45 ]. A research conducted on adolescent students concluded that avoidant coping led to higher levels of distress and that although other methods of coping do not necessarily predict life satisfaction, avoidant coping always inversely predicts life satisfaction [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly associated with higher risk of anxiety, and depression over a period of time [ 43 ]. Other studies have also demonstrated that avoidant coping leads to higher levels of stress and affects wellbeing in a negative way [ 44 , 45 ]. A research conducted on adolescent students concluded that avoidant coping led to higher levels of distress and that although other methods of coping do not necessarily predict life satisfaction, avoidant coping always inversely predicts life satisfaction [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to other studies conducted during the pandemic which confirm that COVID-19 lockdown has affected the mental health of young adults. In particular, the presence of negative coping strategies used by the youth tends to be an indicator of increased levels of stress, anxiety, and depression and it should be considered when planning interventions within this population [14].…”
Section: Personal Factorsmentioning
confidence: 99%
“…old people: Ayalon et al, 2021; Swift & Chasteen, 2021; or young people: see the YOUNG special issue by Bengtsson et al, 2021, and the studies below). Studies on young people have highlighted the impact on physical and mental health (Niedzwiedz et al, 2021; Shaikh et al, 2021; Suarez-Lopez, 2021) and future orientations (Henkens et al, 2022; Kelly et al, 2022; Timonen et al, 2021). Several have also included compliance with COVID-19 restrictions (Jaureguizar et al, 2021; Nearchou et al, 2022; Nivette et al, 2021; Oosterhoff et al, 2020; Padrosa & Bolíbar, 2022; Shaikh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%